An exploratory factor analysis of elicited students' salient beliefs toward critical reading / Nadia Anuar, Ahmad Mazli Muhammad and Zainudin Awang - Anuar, Nadia; Muhammad, Ahmad Mazli; Awang, Zainudin (Universiti Teknologi MARA, 2020)
Critical reading was named a key aspiration in the Malaysian Education Blueprint (2015-2025) and is an essential skill students must acquire. However, an increased number of students was reported to demonstrate poor critical reading performance at the workplace. Thus, Theory of Planned Behaviour (TPB) was utilised to examine students' beliefs critical reading which encompass behavioural belief (advantages and disadvantages of critical reading), normative belief (identification of people who approve participating in critical reading), and control belief (difficulties in critical reading). A three-stage research design was employed. The first stage, elicitation study, was conducted as this stage has received minimum scholarly attention in the TPB literature and to ensure a more comprehensive analysis. The beliefs were analysed qualitatively, which was proceeded by expert panel review. Subsequently, exploratory factor analysis was conducted to determine the validity of the salient beliefs. Findings from the exploratory factor analysis and reliability analysis revealed that beliefs that were elicited from students in this first stage are appropriate and possess sufficient reliability and construct validity. Hence, the results of this study not only contributed to the critical reading and Theory of Planned Behaviour's literature but have also identified more relevant factors that influence students' perception toward critical reading.